The effect of the humidifier on sore throat and cough after thyroidectomy - Jung, Tae Hyeng (The Korean Society of Anesthesiologists, 2011)
BACKGROUND: This study was performed to determine the effects of a humidifier with heated wire circuits on the incidence and severity of postoperative sore throat (POST) and cough after thyroidectomy. METHODS: A total of 61 patients scheduled for elective thyroid surgery under general anesthesia were included in this prospective study. We randomized the patients in to two groups, "without active warming and humidification" (Group C) and "using a heated humidifier" (Group H). The patients were interviewed to obtain the POST and cough scores at 1, 6, 24 and 48 hours after thyroidectomy. RESULTS: The incidence of POST was significantly lower in Group H compared to Group C at 6 hours (57% vs 84%, P = 0.041), 24 hours (37% vs 65%, P = 0.045), and 48 hours (10% vs 52%, P = 0.001). Also the incidence of cough was significantly lower in Group H at 6 hours (27% vs 71%, P = 0.001), 24 hours (13% vs 45%, P = 0.015), and 48 hours (7% vs 32%, P = 0.028). The severity of POST was significantly lower in Group H at all times. In addition, the severity of cough was lower in Group H at other times except at 1 hour. CONCLUSIONS: This result suggests that an active humidification of inspired gases may have the appreciable effect on reducing the incidence and severity of sore throat and cough after thyroid surgery using the endotracheal tube.